The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/microorganisms10050975
|View full text |Cite
|
Sign up to set email alerts
|

Detection of blaOXA-48 and mcr-1 Genes in Escherichia coli Isolates from Pigeon (Columba livia) in Algeria

Abstract: The emergence and spread of β-lactams and colistin-resistant Escherichia coli in birds deserve a special concern worldwide. This study aimed to investigate the presence of β-lactams and colistin-resistant Escherichia coli strains isolated from the faeces of urban and rural pigeons in Batna, Algeria, and to characterise their molecular traits of resistance. Between March and April 2019, a total of 276 faecal droppings samples were collected in Batna, Algeria. Samples were subjected to selective isolation of β-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Based on their findings, they indicate a silent spread of mcr-9 -mediated colistin resistance. The results found for ST224 were confirmed by studies from Algeria, which performed studies on chicken and pigeons [ 56 , 70 ]. The occurrence of ST224 in different hosts and under different conditions may be a reason why it could have displaced the previously detected ST115.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Based on their findings, they indicate a silent spread of mcr-9 -mediated colistin resistance. The results found for ST224 were confirmed by studies from Algeria, which performed studies on chicken and pigeons [ 56 , 70 ]. The occurrence of ST224 in different hosts and under different conditions may be a reason why it could have displaced the previously detected ST115.…”
Section: Discussionsupporting
confidence: 61%
“…Among others, they reported a reduced susceptibility to cefotaxime in 64% of the isolates (273/425). Other studies investigating wild birds confirmed a higher ESBL- E. coli rate in urban settings compared to rural areas, as in a study from Loucif et al [ 56 ]. They found a prevalence of 12% ESBL- E. coli in pigeon in Algeria.…”
Section: Discussionmentioning
confidence: 53%
“…Fortunately, we did not find ST131 in this study, which is in agreement with results reported by other authors [ 13 ]. A wide variety of STs described in E. coli carriers of mcr-1 , ST46, and ST58 reported in this study were previously found in isolates from chickens and the environment [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 72%
“… 61/228 (26.8) bla OXA-48 , bla SHV-145 , bla VIM-2 , bla VIM-4 , bla OXA-181 , bla OXA-23 , bla KPC-2 , bla NDM-5 NA [ 44 ] 2018–2019 Currency coins ST108 E. cloacae 4/12 (33.3) bla OXA-48 NA [ 45 ] 2019 Fresh vegetables Enterobacteriaceae, Pseudomonas spp., Acinetobacter spp. 22/67 (32.8) bla OXA-48 , bla VIM-4 , bla SHV-168 , bla SHV-11 NA [ 46 ] 2019 Fecal samples of pigeon E. coli 14/35 (40) bla OXA-48 NA [ 47 ] NA Organs and feces / cloacal swabs of broiler chickens E. coli 3/39 (7.7) ( iss, hlyF, ompT, iroN, fimC, iutA, elt/est, stx, ipaH, eae, aggR ) NA [ 48 ] Benin 2013 Market Garden Products and Irrigation Water E. coli 25/65 (38.5) ( stx-1, stx-2 ) NA [ 49 ] 2019 Hospital Wastewater Bacteroides spp., Acinetobacter...…”
Section: Resultsmentioning
confidence: 99%